"It's Not My Knee": Understanding Ongoing Pain and Discomfort After Total Knee Replacement Through Re‐Embodiment. Issue 6 (26th March 2022) - Moore, Andrew; Eccleston, Christopher; Gooberman‐Hill, Rachael
Abstract : Objective: Up to 20% of people who undergo total knee replacement surgery have ongoing pain and discomfort. The aim of this study was to understand what role the concepts of embodiment (of both having a body and experiencing the world through one's body) and incorporation (integrating something into one's body) might have in understanding experiences of pain and discomfort after total knee replacement. Methods: We conducted semistructured interviews with 34 people who had received total knee replacement at either of 2 National Health Service hospitals in the UK, and who had chronic postsurgical pain (n = 34, ages 55–93 years). Data were audiorecorded, transcribed, and analyzed thematically. Results: Two main themes were identified: 1) when describing chronic postsurgical pain, some participants also described sensations of discomfort, including heaviness, numbness, pressure, and tightness associated with the prosthesis; 2) participants reported a lack of felt connection with and agency over their replaced knee, often describing it as alien or other, and lacked confidence in the knee. Conclusion: Participants' experiences indicate that some people do not achieve full incorporation of the prosthesis. Our study emphasizes the importance of physicians treating patients as whole people and moving beyond clinical and procedural ideas of success. Our findings suggest that to optimize postoperative outcomes, rehabilitation must focus not only on strengthening the joint and promoting full recovery to tasks but on modifying a person's relationship to the new joint and managing sensations of otherness to achieve full incorporation of the joint or re‐embodiment.